2011
DOI: 10.1101/gr.119636.110
|View full text |Cite
|
Sign up to set email alerts
|

Human population dispersal “Out of Africa” estimated from linkage disequilibrium and allele frequencies of SNPs

Abstract: Genetic and fossil evidence supports a single, recent (<200,000 yr) origin of modern Homo sapiens in Africa, followed by later population divergence and dispersal across the globe (the ''Out of Africa'' model). However, there is less agreement on the exact nature of this migration event and dispersal of populations relative to one another. We use the empirically observed genetic correlation structure (or linkage disequilibrium) between 242,000 genome-wide single nucleotide polymorphisms (SNPs) in 17 global pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
182
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(212 citation statements)
references
References 55 publications
26
182
0
Order By: Relevance
“…We chose European, ND-speaking and YRI populations to trace temporal variation of N e (Supplementary Figure 9). Consistent with the earlier study 56 we found a relatively large N e for YRI, with a slight increase around 9000 years ago, and a population size expansion for Europeans for the last 10 000-12 000 years. All ND-speaking populations except the Avars show a steady decline in their effective population sizes.…”
Section: Inbreeding Coefficient and Roh In Daghestanian Populationssupporting
confidence: 92%
See 2 more Smart Citations
“…We chose European, ND-speaking and YRI populations to trace temporal variation of N e (Supplementary Figure 9). Consistent with the earlier study 56 we found a relatively large N e for YRI, with a slight increase around 9000 years ago, and a population size expansion for Europeans for the last 10 000-12 000 years. All ND-speaking populations except the Avars show a steady decline in their effective population sizes.…”
Section: Inbreeding Coefficient and Roh In Daghestanian Populationssupporting
confidence: 92%
“…r 2 values were binned into 50 genetic distance groups between 0.005 and 0.25 cM in increments of 0.005 cM, and their mean r 2 was used for further calculation of effective population size (N e ). For each population with sample size N ≥ 10 we estimated N e = 1/(4c) × ((1/r 2 ) − 2), where r 2 was adjusted for sample size: (r 2 -1/n) and c is the recombination distance between loci in Morgans 56,57 (1 cM≈1.1-1.2 Mb). The standard error and confidence intervals for N e were derived from separate analysis of each autosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing Malay Project (SSMP) 22 and 36 Indians from the Singapore Sequencing Indian Project (SSIP) 23 were used. These individuals were sequenced on the Illumina HiSeq 2000 at a target depth of 30-fold (Illumina, San Diego, CA, USA), where the alignment and variant calling were performed with CASAVA and SAMtools for the Malay data, and with CASAVA and GATK for the Indians.…”
Section: Comparing Tmrca Estimation J Zhou and Y-y Teomentioning
confidence: 99%
“…16 Another class of methods infers the TMRCA from full chromosomal information, such as CoalHMM, 17 PSMC, 18 and MSMC. 19 The third class of methods essentially infers the TMRCA on the extent of linkage disequilibrium (LD), population diversity measured by the F ST parameter and population allele frequency, such as the approaches by Hayes and colleagues (abbreviated subsequently as T-LD), 20,21 by McEvoy and colleagues (abbreviated subsequently as T-FST), 22 and DADI. 23 These methods differ by the type of input data required (sequence-level information or summary statistics), and by the assumption around the presence of genetic recombination during migration.…”
Section: Introductionmentioning
confidence: 99%